RANCANG BANGUN SISTEM INFORMASI MONITORING BIMBINGAN TUGAS AKHIR BERBASIS WEB MENGGUNAKAN FRAMEWORK REACTJS - La Ode Muhammad Ilham Setiawan; Gunawan; Andi Tenriawaru (Program Studi Ilmu Komputer FMIPA-UHO, 2024)
The thesis guidance process is an important part of the thesis process carried out by students. Guidance is carried out by involving a lecturer with the purpose of informing the achievements that have been achieved in writing the thesis. Based on the results of observations made, the thesis guidance process in the Computer Science Field of Study at Halu Oleo University is still carried out in person so that communication between students and lecturers often occurs. To efficient the process of monitoring the guidance of the thesis of Computer Science Field of Study Program students. ReactJs is a front-end library developed by Meta. The advantages offered by reactJs include speed, convenience and wide scalability. The purpose of this research is to produce an information system for monitoring services for thesis guidance at the Computer Science Field of Study using the ReactJS framework. The reason for choosing reactJs in this research is because of the advantages and advantages it provides. ReactJs can develop single page applications with speed, flexibility and wide scalability. Because of the advantages offered, the reactJs framework is able to help develop the thesis monitoring system more efficiently and quickly. Based on the results of functional testing conducted using blackbox has shown good results, as well as based on the results of testing using the system usability scale conducted on lecturers and students has shown a score of 87 out of 100 with excellent category and A scale for SUS testing lecturers and score 73 out of 100 with Good category and grade scale that is B on SUS testing students. With the level of acceptance for lecturers and students on an accpetable or acceptable scale.